Peningkatan Pemahaman Tentang Politik Uang Bagi Pemilih Pemula Di Kecamatan Kuala Pesisir Kabupaten Nagan Raya - Fadhil Ilhamsyah; Zuhrizal Fadhly; Said Ahmad Kabiru Rafiie; Najamudin Najamudin (Jurnal Pengabdian Masyarakat: Darma Bakti Teuku Umar, 2019)
This paper explains about innovation of the local government which is part of the Population and Civil Registration (Dukcapil) service reform. Aklamasidansa is the policy of the West Aceh Regency in the matter of arranging birth certificates and death certificates that are integrated with village funds. The issue of legal identity is still a problem in Indonesia, many people do not have a legal identity so that it has an impact on all services provided by the government to the community. Aklamasidansa  is an innovation that brings government and society closer. Aklamasidansa has been running since 2017 and operates in the assisted villages. This study used a qualitative method with a case study approach, the informants of this study were the community as recipients of services, the West Aceh government as an innovator. The results of the study show that the aklamasidansa policy has increased the coverage of legal identity ownership, especially birth certificates which increased from 70.25% percent (June 2017) to 93.90 percent (December 2018). Aklamasidansa as one of the service innovations to the community is running very well in improving the data administration of the village and make it easier for citizens to receive services in arranging birth certificates and death certificates.